Enlarging the European Union: The short-term success of incrementalism and de-politicisation - Gerda Falkner; Michael Nentwich (Max Planck Institute for the Study of Societies, 2000)
This paper analyses the most important issues of the EU enlargement process. We first discuss an empirical paradox involved in enlargement: the obvious development of the original European Communities into a Union with important supranational features and ever more policy clout has by no means discouraged aspirant member states. Why is it that more and more states are willing to give up much of their otherwise cherished national sovereignty by joining this Union, knowing that even more sovereignty will be eroded over time? Then we address the major challenges the EU has to face before actually widening any further, in particular concerning financial and institutional issues as well as internal and external boundaries. The concluding section discusses implicit and explicit EU enlargement strategies of past and present times. We argue that there is a danger that the incrementalist and de-politicised character of the recent enlargement (non-)discussions are successful only in the short term while actually being rather dangerous in the longer run. – – Dieser Artikel analysiert die wesentlichsten Themen des EU-Erweiterungsprozesses. Zunächst diskutieren wir das empirische Paradox der Erweiterung, nämlich daß sich zwar einerseits die ursprünglichen Europäischen Gemeinschaften in eine Union mit wichtigen supranationalen Befugnissen und immer mehr politischer Durchsetzungskraft entwickelt hat, dies aber die Erweiterungskandidaten keineswegs abgeschreckt hat. Warum sind immer mehr Staaten bereit, ihre ansonsten gehegte nationale Souveränität durch einen Beitritt zur Union aufzugeben, während sie sich sogar dessen bewusst sind, daß auch weiterhin noch mehr Souveränität abzugeben sein wird? Anschließend widmen wir uns den wichtigsten Herausforderungen, denen sich die EU vor der anstehenden Erweiterungsrunde stellen muß, nämlich den finanziellen und institutionellen Fragen wie auch der Festlegung ihrer internen und externen Grenzen. Der abschließende Teil diskutiert die früheren und aktuellen (sowohl impliziten wie auch expliziten) Erweiterungsstrategien der EU. Wir weisen darauf hin, daß der inkrementelle und entpolitisierte Charakter der jüngsten Beitrittsdiskussion zwar kurzfristig erfolgreich scheint, aber langfristig gefährlich sein könnte.
Keywords: 300